Biofilm Formation Reduction by Eugenol and Thymol on Biodegradable Food Packaging Material - Pleva, Pavel; Bartošová, Lucie; Máčalová, Daniela; Zálešáková, Ludmila; Sedlaříková, Jana; Janalíková, Magda (Foods (Basel, Switzerland), 2021)
Biofilm is a structured community of microorganisms adhering to surfaces of various polymeric materials used in food packaging. Microbes in the biofilm may affect food quality. However, the presence of biofilm can ensure biodegradation of discarded packaging. This work aims to evaluate a biofilm formation on the selected biodegradable polymer films: poly (lactic acid) (PLA), poly (butylene adipate-co-terephthalate) (PBAT), and poly (butylene succinate) (PBS) by selected bacterial strains; collection strains of Escherichiacoli, Staphylococcusaureus; and Bacillus pumilus, Bacillussubtilis, Bacillustequilensis, and Stenotrophomonasmaltophilia isolated from dairy products. Three different methods for biofilm evaluation were performed: the Christensen method, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, and fluorescence microscopy. High biofilm formation was confirmed on the control PBS film, whereas low biofilm formation ability was observed on the PLA polymer sample. Furthermore, the films with incorporated antimicrobial compounds (thymol or eugenol) were also prepared. Antimicrobial activity and also reduction in biofilm formation on enriched polymer films were determined. Therefore, they were all proved to be antimicrobial and effective in reducing biofilm formation. These films can be used to prepare novel active food packaging for the dairy industry to prevent biofilm formation and enhance food quality and safety in the future.
Keywords: biofilm; biodegradable polymers; food packaging; antimicrobial activity